Thermalization dynamics of the quark condensate under strong magnetic fields - Frazon, Arthur Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Strong magnetic fields affect quantum chromodynamics (QCD) properties in many situations, such as the early universe, magnetars, and heavy-ion collisions. A~QCD property affected by strong magnetic fields is the chiral quark condensate, an approximate order parameter of the QCD transition between a high-temperature quark-gluon phase and a low-temperature hadronic phase. In this dissertation, we studied numerically the thermalization dynamics of the quark condensate using a Langevin field equation derived by Krein and Miller in Symmetry 13, 551 (2021). The condensate is represented by the scalar-isoscalar field of the linear sigma model with quarks. Using the closed-time path formalism of nonequilibrium quantum field theory, the Langevin field equation is obtained by integrating out the quarks in a mean-field approximation. We solved numerically this equation within a quench scenario, in that the temperature of the system suddenly changes from a high temperature, at which the vaue of the condensate is very small, to low temperatures for which its value is nonzero. We showed that the solutions display an explosive initial growth and then damped oscillations toward an equilibrium value. The damping is determined by a dissipation coefficient that is due to the decay of the condensate into quark-antiquark pairs. The magnetic field has a dramatic effect on the dissipation coefficient, producing a considerably different thermalization scenario than thermalization in the absence of the field.

Campos magnéticos fortes afetam propriedades da cromodinâmica quântica (QCD) em muitas situações, como no universo primitivo, magnetares e colisões de íons pesados. Uma propriedade da QCD afetada por campos magnéticos fortes é o condensado de quarks quiral, um parâmetro de ordem aproximado da transição da QCD entre uma fase quark-glúon a altas temperaturas e uma fase hadrônica a baixas temperaturas. Nesta dissertação, estudamos numericamente a dinâmica de termalização do condensado de quarks usando uma equação de campo de Langevin derivada por Krein e Miller em Symmetry 13, 551 (2021). O condensado é representado pelo campo escalar-isoescalar do modelo sigma linear com quarks. Usando o formalismo “closed-time path” da teoria quântica de campos de não-equilíbrio, a equação de campo de Langevin é obtida integrando os quarks em uma aproximação de campo médio. Resolvemos numericamente essa equação de Langevin dentro de um cenário de quench de temperatura, em que a temperatura do sistema muda repentinamente de uma temperatura alta, na qual o valor do condensado é muito pequeno, para temperaturas baixas para as ele é diferente de zero. Mostramos que as soluções apresentam um crescimento inicial explosivo e depois oscilações amortecidas em direção a um valor de equilíbrio. O amortecimento é determinado por um coeficiente de dissipação devido ao decaimento do condensado em pares de quark-antiquark. O campo magnético tem um efeito dramático no coeficiente de dissipação, produzindo um cenário de termalização consideravelmente diferente da termalização na ausência do campo.
Dinâmica de termalização do condensado de quarks sob campos magnéticos fortes
Keywords: QCD (Nuclear Physics); Chiral Symmetry; Quark Condensate; QCD Phase Transitions; Magnetic Fields in QCD; Cromodinâmica Quântica; Transições de Fase (Física Estatística); Simetria Quiral; Quarks